2014
DOI: 10.1111/dsji.12023
|View full text |Cite
|
Sign up to set email alerts
|

Norming of Student Evaluations of Instruction: Impact of Noninstructional Factors

Abstract: Student Evaluations of Instruction (SEIs) from about 6,000 sections over 4 years representing over 100,000 students at the college of business at a large public university are analyzed, to study the impact of noninstructional factors on student ratings. Administrative factors like semester, time of day, location, and instructor attributes like gender and rank are studied. The combined impact of all the noninstructional factors studied is statistically significant. Our study has practical implications for admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…It is also recommended to use validated instruments for data collection to circumvent a potential measurement bias (Nargundkar & Shrikhande, 2014). To measure the tool interactivity, we adopted six measurement dimensions of perceived user‐to‐system interactivity developed by Leiner and Quiring (2008).…”
Section: Methodsmentioning
confidence: 99%
“…It is also recommended to use validated instruments for data collection to circumvent a potential measurement bias (Nargundkar & Shrikhande, 2014). To measure the tool interactivity, we adopted six measurement dimensions of perceived user‐to‐system interactivity developed by Leiner and Quiring (2008).…”
Section: Methodsmentioning
confidence: 99%
“…In a provocative article, Bauerlein () suggested that research should only count one‐sixth or even zero toward tenure, while the weight attached to teaching should rise proportionally. Nargundkar and Shrikhande () found that nontenure track faculty in business schools had significantly higher student evaluation ratings than tenure track (untenured) faculty. Perhaps the difference is due to different incentive structures.…”
Section: Recommendationsmentioning
confidence: 99%
“…In the evaluation literature, there are relatively few studies that look at factors affecting evaluations in colleges of business and engineering. The research presented here distinguishes itself from previous research in business (e.g., Nargundkar & Shrikhande, ; Peterson et al., ), and adds to the body of knowledge in several ways. First, it specifically contrasts data from a college of business and a college of engineering, showing the differences in the effects of various factors on SET.…”
Section: Introductionmentioning
confidence: 81%
“…Prior work has also examined the effect of SET on whether students are required to take a specific course (core) or whether they are taking the course as an elective. Some research has shown that instructors teaching elective courses receive higher SET scores than those for core courses (e.g., Aleamoni & Thomas, ; Gage, ; Kapel, ; Lovell & Haner, ; Nargundkar & Shrikhande, ). Isely and Singh () and McPherson and Jewell () found a correlation between low SET scores and the proportion of students taking core (required) rather than elective courses.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%